Evaluation of DTTV Positioning Based on Measurement Data - Promwong, Sathaporn; Southisombat, Khamphoui; Suwansukho, Nattapan (My University, 2022)
Positioning uses radio waves such as AM, FM, telephone, and wireless signals. Which have been studied by many research for this thesis, consider finding positions using signals. The digital terrestrial television signal was used for positioning. The measurement model is designed with 121 positions covering an area of lO× 10 square meters by installing an antenna receiving height of 1 meter for reference height and 6 meters as specified by the NBTC. The distance from the transmit antenna to the receiving antenna is about 26 kilometers, using spectrum analyzers to measure and collect the results for analysis and compare the distance errors by using a fingerprinting technique and clean algorithm and a clean algorithm to get the most suitable signal. It can be seen that the distance error is reduced. So, it will be more accurate and the basis for future studies. Moreover, it can locate more accurately using digital terrestrial television signals, The DVB-T2 standard digital terrestrial television signal and fingerprinting technique, and the CLEAN algorithm.
Keywords: CLEAN algorithm; DTTV; DVB-T2; outdoor localization